An exploration of the word 'palliative' in the 19th century: searching the BMJ archives for clues. Issue 1 (14th November 2012) - Taubert, Mark; Fielding, Helen; Mathews, Emma; Frazer, Ricky
Abstract : Background: Palliative care went through a significant evolution in the 20th century, but the 19th century has been seen my some scholars as the real turning point toward the more modern concept of hospices and palliative care. Methods: To investigate some examples of earlier uses of the word 'palliative', a literature search was conducted within the earliest available BMJ archive sections, the years 1840 to 1842. This provided a glimpse into how the word was used in the medical literature in Victorian times, mid-nineteenth century. Results: Search results brought up a number of case reports, and the word was employed to describe medicines ('use of palliatives') as well as passive, non-active treatment approaches, probably best described as a watch-and-wait strategy. Of note is that the first recorded use of the word in the archives is by a surgeon. Conclusions: Some doctors associated the word palliative with there not being any prospect for cure and only for the relief of symptoms and greater comfort of the patient. There were, however, early reflections on whether palliative treatments may in some cases increase the length of patients' lives.